Students' Skills to Make Inductions and Consider Inductions to Explain the Phenomenon of the Volta Cell - Albaiti, A (PT FORMOSA CENDEKIA GLOBAL, 2024)
Make induction and consider induction descriptor is one of important critical thinking skills for students in order to succeed facing dynamic and complex world. The purpose of this study was to improve the students’ make induction and consider induction skills (MICIS) through voltaic cell laboratory activities based on their mental models. It was also to know the excellence dan the limitations of this learning. It was a weak experimental design with one group pretest posttest design. The study involved 12 students who took General Chemistry II, one of university in Papua. The instruments were essay test, observation sheet, students’ worksheet, and questioners. Essay test of 2 items was used to analyze their MICIS that calculated by N-Gains value. Each items was designed to interconnect macroscopic, sub-microscopic, and symbolic levels. Students’ MICIS (was increased through this learning (N-gain=63,75%). It is necessary to interconnect the three level of chemistry representation level for increasing the students’ MICIS in studying chemistry.